CLINICAL EVALUATION OF TENCKHOFF CATHETER INSERTION IN PAEDIATRIC PERITONEAL DIALYSIS : A SINGLE CENTER STUDY - Nurkholiq, Syahdat; Ghinorawa, Tanaya (Indonesian Journal of Urology, 2021)
Objective: This study aimed to evaluate the clinical outcome of Tenckhoff catheter insertion at Sardjito General Hospital for pediatric renal failure. Material & Methods: Data were collected from January 2014 to December 2018 at Sardjito General Hospital. All patient records were collected retrospectively such as patient characteristics, underlying diseases of kidney failure, congenital abnormalities, surgical technique, complications that occur after Tenckhoff catheter insertion. Results: 45 patients meet the inclusion criteria. A total of 7 patients with acute kidney failure (15.5%) and 38 patients with chronic kidney failure (84.5%). Glomerulonephritis is the most common cause of kidney failure (21 patients, 46.7%). The insertion technique used was open surgery in 34 patients (76%) and laparoscopic insertion in 11 patients (24%). Complications reported were catheter dysfunction, leakage of dialysate, surgical site infection, and peritonitis. Conclusion: Tenckhoff catheter insertion for peritoneal dialysis (PD) in pediatric patients with acute and chronic renal failure performed in our center is effective and safe. The most common cause of renal failure in pediatric is glomerulonephritis. Open surgery and laparoscopic insertion of Tenckhoff catheter both have a low complication rate. Catheter dysfunction due to mechanical catheter obstruction is one of the main problems in the placement of Tenckhoff catheter.